Placental (pro)renin receptor expression and plasma soluble (pro)renin receptor levels in preeclampsia. (January 2016) - Nartita, Tatsuya; Ichihara, Atsuhiro; Matsuoka, Kikumi; Takai, Yasushi; Bokuda, Kanako; Morimoto, Satoshi; Itoh, Hiroshi; Seki, Hiroyuki
Abstract: Introduction: The prorenin receptor ((P)RR) contributes to the regulation of the tissue renin-angiotensin system (RAS) and the function of V-ATPase, which are essential for Wnt signaling. Thus, (P)RRs may be involved in the control both of feto-placental and maternal circulation during pregnancy. This study was conducted to clarify how placental (P)RR expression and plasma soluble (P)RR [s(P)RR] levels are associated with blood pressure elevations and renal function during pregnancy. Methods: We conducted a cross-sectional study, conducted at Saitama medical center in 2010–2013. Preeclamptic women (n = 16) diagnosed according to the criteria of Japan Society of Obstetrics and Gynecology and normotensive pregnant women (n = 15) participated in the study. We measured the expression of (P)RR in the placenta, plasma s(P)RR levels, systolic blood pressure (SBP), and estimated glomerular filtration rate (eGFR). Results: Placental expression of (P)RR was significantly higher in preeclamptic women than in normotensive pregnant women. The plasma s(P)RR levels were significantly higher in preeclamptic women than in normotensive pregnant women. Systolic blood pressure (SBP) was positively correlated with placental (P)RR levels ( P = 0.0001) and plasma s(P)RR levels ( P = 0.005) in all pregnant women. In preeclamptic women, SBP was positively correlated with placental (P)RR levels ( P = 0.004), but not with plasma s(P)RR levels ( P = 0.15). The eGFR was negatively correlated with placental (P)RR levels ( P = 0.02) and plasma s(P)RR levels ( P = 0.0002) in all pregnant women. In preeclamptic women, eGFR was negatively correlated with plasma s(P)RR levels ( P = 0.006), but not with placental (P)RR levels ( P = 0.93). Discussion: Placental (P)RR can be involved in blood pressure regulation via the tissue RAS. On the other hand, plasma s(P)RR may be involved in the pathogenesis of decreased renal function in preeclampsia. Highlights: The prorenin receptor ((P)RR) may contribute to pathogenesis of preeclampsia. Placental expression of (P)RR was significantly elevated in preeclampsia. The plasma s(P)RR level was significantly elevated in preeclampsia. Systolic blood pressure was correlated with placental (P)RR and plasma s(P)RR. The estimated GFR was correlated with placental (P)RR and plasma s(P)RR.